If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = x + 27 Reorder the terms: 2x = 27 + x Solving 2x = 27 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2x + -1x = 27 + x + -1x Combine like terms: 2x + -1x = 1x 1x = 27 + x + -1x Combine like terms: x + -1x = 0 1x = 27 + 0 1x = 27 Divide each side by '1'. x = 27 Simplifying x = 27
| -2+4k=34 | | 9-4b=13 | | -9-7b=-79 | | -3a+10=4 | | -2+4m=10 | | -6-7t=-6 | | 9+2d=1 | | -2n+10=18 | | -6n-7=-79 | | 7k-10=60 | | 2-5a=37 | | 9S+8-S=2(2S+8) | | 4k+5=53 | | -2k-6=4 | | 4+5a=-51 | | -2+2d=6 | | 5k+2=7 | | 7a-10=-80 | | 4-2b=0 | | -7+7n=77 | | 9+2d=15 | | 4b+6=-30 | | 2+2w=18 | | 3+2t=17 | | 8+7w=22 | | 2t+3=23 | | 6n+1=43 | | -4m+4=-4 | | a+20=2a+10 | | 4a^2+4a-3=0 | | 5a-5=45 | | 1+4m=29 |